Brazilian version of the Profil der Lebensqualität Chronischkranker: validity and psychometric evidences for climacteric women - Eliane Araújo de Oliveira; Maria del Carmen Villaverde Gutiérrez; Suellen Marinho Andrade; Rebeca Vinagre Martins; Johannes Siegrist (Acta Scientiarum. Health Sciences, 2015)
The main objective of this study was to validate and examine the psychometric parameters of Profil der Lebensqualität Chronischkranker (PLC) in climacteric women. We conducted an exploratory research in Health Care and Treatment enrollment 280 participants. The data collection instruments were the PLC and the SF-36 (Medical Outcomes Study 36 - Item Short - Form Health Survey). The original German version of PLC consists of 40 items that explore the biological and psychosocial items of daily life. The questionnaire was submitted to translation into Portuguese of Brazil, back translation, review by experts and cultural adaptation. For the psychometric study, Cronbach's alpha, factor analysis and the Pearson correlation coefficient were used.In the internal consistency analysis, Cronbach's alpha coefficient ranged from 0.81 a 0.89 in all categories, indicating that the instrument has adequate internal consistency. We could verify the existence of five factors that together explained 55.85% of total variance. For criterion validity, Pearson’s correlation was between 0.41 and 0.78. Therefore, the Brazilian version of the PLC is configured in valid, reliable and easy-to-use option for assessment of quality of life in climacteric women.